A field-based study of metabolites in sacculinized king crabs Paralithodes camtschaticus (Tilesius, 1815) and Lithodes aequispinus Benedict, 1895 (Decapoda: Anomura: Lithodidae). Issue 6 (7th September 2018) - Zacher, Leah S; Horstmann, Lara; Hardy, Sarah M
Abstract: Parasitic barnacles, the Rhizocephala, infect and castrate their crustacean hosts, causing changes in host morphology, physiology, and behavior. The physiological processes by which rhizocephalans manipulate their hosts are not well understood. We used an untargeted LC-MS metabolomics approach to compare the metabolite profiles (e.g., small molecules such as signaling molecules and other products of metabolism) of lithodid crabs with and without rhizocephalan infections. We tested whether metabolite changes caused by rhizocephalan infection could be detected in the hemolymph, muscle, and hepatopancreas of the red king crab Paralithodes camtschaticus (Tilesius, 1815) and the hemolymph of the golden king crab Lithodes aequispinus Benedict, 1895 infected by the rhizocephalans Briarosaccus regalis Noever, Olson & Glenner, 2016 and B. auratum Noever, Olson & Glenner, 2016, respectively. Tissue and hemolymph samples were collected from both species of king crabs between 2013 and 2015 in southeast Alaska. Hundreds of potential metabolites were identified in all analyzed tissues, yet few differed with crab sex and no metabolites could differentiate infected and healthy crabs, regardless of sex. There were large variations in the crab metabolome according to collection year and location, which likely masked differences related to sex and infection status. This environmental-metabolomics approach suggests that the crab metabolome may be greatly influenced by environmental variation. Future studies in a more controlled environment will be necessary to further unravel how the host crab metabolome changes with rhizocephalan infection.